A new formula for premature infants: effects on growth and nutritional status. (August 2015) - Marseglia, Lucia; Pagano, Giuseppina; Arco, Alessandro; Barberi, Ignazio; Biasucci, Giacomo; Riboni, Sara; Mondello, Isabella; Fiamingo, Chiara; Moro, Guido
Abstract Objective: Nutritional management influences immediate survival as well as subsequent growth and development of low birth weight and very low birth weight infants. Preterm infant formula (PTF) is used when there is an inadequate supply of mother's milk or when the mother is unable to breastfeed and donor breast milk is unavailable. The purpose of this prospective multicenter study was to evaluate short-term effects on nutritional status (auxological and biochemical parameters) in a population of premature infants who received a preterm infant formula. Methods: Ninety-seven preterm infants with a birth weight between 500 g and 2000 g and a gestational age of 25–34 weeks postmenstrual age were randomly assigned to received a new preterm infant formula (Nutribèn Pre), and their nutritional status were compared to 75 fortified human milk (FHM) fed infants. Results: No significant differences were observed between FHM and Nutribèn Pre fed infants in terms of growth, feeding tolerance and biochemical profiles. Conclusion: Nutribèn Pre is a valid, effective and safe alternative for the nutrition of preterm infants.